Arborização urbana : espécies arbóreas nativas e a captura do carbono atmosférico - Muneroli, Clenara Citron (2009)
The objective of this research is to elaborate environmental criteria for an urban arborization in the subtropical damp region of the country, emphasizing the aspects of the pollution improvement in the city environment, mainly, concerning the carbon capture, the trees do through photosynthesis. There are many benefits, a well thought-out urban arborization offers to the city environment; not only in relation of the environmental aspect but also in relation of the quality population life. The native vegetation also appeals inside urban environment; because it presents important characteristics concerning its environmental development and performance, in the forests as well as in the cities, because they are appropriate to our latitude, climate and morphology. This is the original contribution this research proposes, beyond systematizing he reading about the subject as a grounding for future studies. The proposal is to use two stud places of the matter in Carazinho city, RS, in a residential neighborhood with a low occupation density of the urban soil and another with a higher density. To develop the study of this matter, a survey of the current situation of the neighborhood was done to analyze the proposed subject and to proceed the checking about the aspects of the environmental interest, counted in the field work, mainly those related to the efficiency of the native arboreous species in the infra-structure net and n the carbon dioxide capture. The selection of some arboreous species to carry out the photosynthesis is a predominant fact, so that these apecies are incorporated to the local urban arborization